Ramadan fasting: Does it good for normal, overweight and obese subjects? - Abu Bakar, Ibrahim; Ali Khan Khattak, Muhammad Muzaffar; Nazri Shaharuddin, Mohd Firdaus; Ahmad, Nur Syamimi (2010)
During the holy month of Ramadan, Muslims refrain from drinking and eating starting from sunrise until sunset. This study was designed to evaluate the effect of Ramadan fasting on anthropometric, energy and macro & micro-nutrients intake changes of normal, overweight and obese subjects. A total of sixty seven volunteers aged between 19-24 years old from International Islamic University Malaysia (IIUM) Kuantan campus were randomly recruited using convenience sampling method before Ramadan 2009. The subjects were categorized to normal (BMI 18.5-24.9), overweight (BMI 25.0-29.9) and obese (BMI≥30). Their height, weight, waist and hip circumference as well as their body fat percentage were recorded on the first day and on the 21th day of Ramadan. Each subject was also asked to record his/her three days food intake, once during pre-fasting week and another was during the third week of Ramadan. The food intake data were then analysed using Malaysian Food Composition Table and Food Atlas to get the average amount of energy intake as well as macro & micro-nutrients intake. The collected data were then analysed using statistical software SPSS 15.0. After 21 days of fasting, the results showed significant reduction (p<0.05) in body weight and waist-to-hip ratio of normal and overweight & obese subjects. BMI and body fat percentage in both normal and overweight & obese subjects were decreased but not significantly different at P≥0.05. The mean daily energy intake before and during Ramadan were not significantly different (P≥0.05) however, both values were found below the suggested daily energy intake for Malaysian of similar age. The mean daily energy expenditure before and during Ramadan were also not significantly different (P≥0.05). The intake of carbohydrate was significant decreased (P<0.05) in Ramadan but protein and fat intake were significant increased (P<0.05) compared to pre-fasting week of Ramadan. There was significant increased (p<0.05) in the intake of vitamin A, C and phosphorus during Ramadan. This study showed that Ramadan fasting give positive effects in term of body weight reduction of normal, overweight and obese subjects.